1971
DOI: 10.1113/jphysiol.1971.sp009430
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and ADH secretion in relation to electrical activity in antidromically identified supraoptic and paraventricular units

Abstract: SUMMARY1. Electrical recordings were made from antidromically identified supraoptic and paraventricular units during intracarotid injections of hypertonic and isotonic sodium chloride solutions in rats.2. The blood concentrations of vasopressin and oxytocin were estimated by bio-assay before and at different intervals after similar injections.3. Although a significant change in the action potential activity of the supraoptic nucleus was associated with hormone release, the results were not entirely consistent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

1972
1972
1987
1987

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(58 citation statements)
references
References 14 publications
2
54
1
1
Order By: Relevance
“…The existence of such a system in mammalian neurosecretory cells of the SON and PVN has also been indicated, first by Koizumi & Yamashita in 1969. Inhibition of cell activity by antidromic stimulation of the posterior pituitary has been demonstrated now in the rat SON (Kelly & Dreifuss, 1970), and cat SON and PVN and in the SON and PVN of the dog , 1971. The IPSPs recorded intracellularly from the dog SON and evoked by antidromic stimulation is good evidence to suggest the existence of a recurrent collateral system in these nuclei , 1971. The demonstrated presence ofsmall cells which resemble Renshaw cells (the recurrent collateral cells of the spinal cord) provides additional evidence of interaction through recurrent collaterals.…”
Section: Problem Of Recurrent Collateralmentioning
confidence: 99%
See 3 more Smart Citations
“…The existence of such a system in mammalian neurosecretory cells of the SON and PVN has also been indicated, first by Koizumi & Yamashita in 1969. Inhibition of cell activity by antidromic stimulation of the posterior pituitary has been demonstrated now in the rat SON (Kelly & Dreifuss, 1970), and cat SON and PVN and in the SON and PVN of the dog , 1971. The IPSPs recorded intracellularly from the dog SON and evoked by antidromic stimulation is good evidence to suggest the existence of a recurrent collateral system in these nuclei , 1971. The demonstrated presence ofsmall cells which resemble Renshaw cells (the recurrent collateral cells of the spinal cord) provides additional evidence of interaction through recurrent collaterals.…”
Section: Problem Of Recurrent Collateralmentioning
confidence: 99%
“…Several papers have now appeared describing studies of neurosecretory cells of the SON and the PVN which were identified by antidromic excitation (Kelly & Dreifuss, 1970;Yamashita, Koizumi & Brooks, 1970;Barker, Crayton & Nicoll, 1971;Dyball, 1971). However, none of these publications were concerned with the neural control of neurosecretory cell activity from other structures nor did they report intracellular recordings from mammalian neurosecretory cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The osmoreceptors, have not been identified, but evidence from unit recordings suggests that the neurosecretory cells themselves may respond to a rise in the osmolarity of the blood. The firing rate of these cells is frequently accelerated by hypertonic stimuli (Koizumi, Ishikawa & Brooks, 1964;Wang, 1969), although this effect is not necessarily accompanied by a rise in hormone output (Dyball, 1971). It is possible that a process involving neurotransmitters, intervenes between the stimulus and the release of APR (Bridges & Thorn, 1970).…”
Section: Introductionmentioning
confidence: 99%